Fascia Iliaca Compartment Block for Perioperative Pain Management of Geriatric Patients with Hip Fractures: A Systematic Review of Randomized Controlled Trials - Hao-yang Wan; Su-yi Li; Wei Ji; Bin Yu; Nan Jiang (Pain Research and Management)
Background. With continuous increase of the aging population, the number of geriatric patients with fragility hip fractures is rising sharply, and timely surgery remains the mainstay of treatment. However, adequate and effective pain control is the precondition of satisfactory efficacy. This systematic review aimed to summarize the use of fascia iliaca compartment block (FICB) as an analgesic strategy for perioperative pain management in geriatric patients with hip fractures. Methods. PubMed and Embase databases were searched for English published randomized controlled trials (RCTs) reporting application of FICB for pain control of the older adults with hip fractures between January 1st, 2000, and May 31st, 2020. The modified Jadad scale was used to evaluate quality of the RCTs included. Primary outcomes of the eligible RCTs were presented and discussed. Results. A total of 27 RCTs with 2478 cases were included finally. The present outcomes suggested, after admission or in the emergency department (ED), FICB can provide patients with equal or even better pain relief compared with the conventional analgesia methods, which can also reduce additional analgesic consumptions. While, before positioning for spinal anesthesia (SA), FICB is able to offer superior pain control, facilitating SA performance, after surgery FICB can effectively alleviate pain with decreased use of additional analgesics, promoting earlier mobilization and preventing complications. Conclusions. FICB is a safe, reliable, and easy-to-conduct technique, which is able to provide adequate pain relief during perioperative management of geriatric patients with hip fractures.